Notas para un catálogo del corpus epistolar del helenista Vicente Mariner - Rodríguez Herrera, Gregorio (1995)
El objeto del presente trabajo es ofrecer un catálogo de las 77 cartas que constituyen actualmente el corpus epistolar de Vicente Mariner. En éste se indica la localización, destinatario y lengua utilizados en las epístolas.
In this work we aim to present a catalogue made up of 77 letters which constitute Vicente Mariner’s epistolary corpus. The catalogue provides information about the repositories where letters are kept, their addresseés as well as tbe languages used.
Keywords: Mariner, Vicente; Cartas